Waste heat recovery systems for internal combustion engines: classification and benefits - Marchenko, A.; Samoilenko, D.; Adel Hamzah, Ali; Adel Hamzah, Omar (НТУ "ХПИ", 2014)
Recent trend about the best ways of using the deployable sources of energy in to useful work in order to reduce the rate of consumption of fossil fuel as well as pollution. Out of all the available sources, the internal combustion engines are the major consumer of fossil fuel around the globe. The remaining heat is expelled to the environment through exhaust gases and engine cooling systems, resulting in to entropy rise and serious environmental pollution, so it is required to utilized waste heat into useful work. The recovery and utilization of waste heat not only conserves fuel, usually fossil fuel but also reduces the amount of waste heat and greenhouse gases damped to environment. It is imperative that serious and concrete effort should be launched for conserving this energy through exhaust heat recovery techniques. Such a waste heat recovery would ultimately reduce the overall energy requirement and also the impact on global warming.

Среди энергетических установок, представленных в мире, ДВС является основным потребителем ископаемых топлив. Теплота и энергия отработавших газов ДВС, а также теплота, отводимая с охлаждающей жидкостью приводят к росту энтропии и загрязнениям окружающей среды. Использование этой теплоты для получения полезной работы – один из путей снижения нагрузки на окружающую среду. Рассмотрены основные методы утилизации вторичной теплоты ДВС. Выполнена их классификация и оценка эффективности.
Системы утилизации энергии отработавших газов ДВС: классификация и преимущества
Keywords: deployable sources of energy; fossil fuel; pollution; available sources